Analysis of profitability and resource use efficiency among banana farmers in Chitwan, Nepal - Shrestha , Suman; Thakali , Roshan; Kandel , Santosh; Subedi , Roshan (Journal of Agriculture and Natural Resources, 2025)
Banana is a high value crop with immense potential to enhance production through area expansion and improved production practices. This study aimed to investigate the profitability and resource use efficiency of banana enterprises in Chitwan, Nepal. Primary data were obtained from 135 banana growers and 45 traders by using semi-structured questionnaire. Descriptive and inferential statistics, along with the Cobb Douglas production function, were used to estimate resource allocation. The study reported average gross profit of 5211.65/kattha and benefit cost ratio of 1.52, indicating that banana farming is profitable. The analysis of resource use efficiency showed the under-utilization of plantation, chemical fertilizers, and micronutrients, while farm-yard manure, labor, pesticide, and irrigation were overutilized. For the optimum allocation of resources, the cost of plantation, chemical fertilizers, and micronutrients needs to be increased by 59%, 14%, and 46%, respectively, while the cost of farmyard manure, labor, pesticide, and irrigation needs to be decreased by 209%, 250%, 194%, and 84%, respectively. Disease, insect and weed infestation were the main problem. during production, while the domination by middle men was found as the major issues for marketing.  The study recommends enhancing extension services through better technologies and training in optimizing inputs.